Additive manufacturing manganese-copper alloy and preparation method and application thereof

By optimizing the manganese-copper alloy powder composition and laser selective melting parameters, combined with substrate preheating, the solidification crack problem of manganese-copper alloy in laser additive manufacturing was solved, the preparation of high-performance manganese-copper alloy was achieved, and the forming quality and damping performance of the material were improved.

CN120587489AActive Publication Date: 2025-09-05GUANGDONG INST OF NEW MATERIALS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511086629.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-09-05
Estimated Expiration
2045-08-05

AI Technical Summary

Technical Problem

During the laser additive manufacturing process of manganese-copper alloy, the powder undergoes a non-equilibrium thermal cycle of rapid melting, which easily produces defects such as unfused materials, pores, and solidification cracks, resulting in a decrease in the mechanical properties of the material and reduced damping performance, limiting its application in the field of engineering vibration reduction.

Method used

By optimizing the composition of manganese-copper alloy powder, adding nickel elements, and combining it with laser selective melting technology, the scanning strategy, scanning interval time and substrate preheating temperature are adjusted to control the microstructure, reduce residual stress and eliminate solidification cracks.

Benefits of technology

The preparation of high-performance manganese-copper alloys with good forming quality, density, damping performance and mechanical properties was achieved, which reduced production costs and avoided subsequent heat treatment steps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120587489A_ABST
    Figure CN120587489A_ABST
Patent Text Reader

Abstract

The invention discloses an additive manufacturing manganese-copper alloy and a preparation method and application thereof.The preparation method mainly utilizes a selective laser melting technology to prepare the manganese-copper alloy, the components of the manganese-copper alloy are optimized by adding nickel elements, and printing process parameters are optimized, the preheating temperature of a substrate, the scanning interval time and a scanning strategy are controlled, so that the additive manufacturing manganese-copper alloy is obtained. According to the method, the microstructure of the manganese-copper alloy can be effectively regulated and controlled, reduction of residual thermal stress generated in the rapid melting and cooling forming process of manganese-copper alloy powder is facilitated, solidification cracks generated in the printing forming process are effectively eliminated, and the alloy has good forming quality, high density and combination of good damping performance and mechanical performance. According to the method, post-heat treatment is not needed, the high-performance manganese-copper damping alloy is prepared in one step, and the production cost is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to an additively manufactured manganese-copper alloy and a preparation method and application thereof. Background Art

[0002] With the continuous advancement of industrial technology, various types of mechanical equipment are developing in the direction of high speed, high efficiency and automation, but the vibration and noise problems caused by this are becoming increasingly prominent. Mechanical vibration not only accelerates equipment fatigue damage and shortens its service life, but also affects the machining accuracy of parts. In severe cases, it may even cause catastrophic accidents. Traditional vibration reduction methods mainly use two approaches: system vibration reduction and structural vibration reduction. However, these methods often lead to increased equipment size, weight and cost. In contrast, damping alloy materials convert vibration energy into heat energy dissipation through their own microstructure, which has the unique advantage of reducing vibration and noise at the source. They also have excellent processing performance, a wide applicable temperature range, and good frequency adaptability.

[0003] Manganese-copper alloys, a class of functional materials with excellent damping and mechanical properties, have been successfully applied in a variety of vibration and noise reduction applications, including automotive manufacturing, ship propellers, and precision instruments. Their damping performance primarily stems from the movement of twin interfaces within the material and the movement of the interface between martensite twins and the parent phase. These interfacial motions dissipate mechanical vibration energy by converting it into heat. This twin structure forms during the diffusionless phase transformation from FCC austenite to FCT martensite, and the martensite transformation temperature is highly dependent on the manganese content. When the manganese content is below 82 at.%, the martensite transformation temperature drops below room temperature, resulting in a lack of twin martensite, the damping source, at room temperature, and thus reduced damping performance. To improve this, a solution treatment at 750-950°C is commonly used, followed by water quenching to room temperature to obtain a supersaturated FCC solid solution, followed by aging heat treatment at 350-500°C. The spinodal decomposition occurring during the aging process forms a Mn-rich matrix and Cu-rich nanoparticles, which promote the occurrence of martensitic phase transformation.

[0004] In recent years, selective laser melting (SLM) technology has gained widespread application in industrial manufacturing due to its unique advantages. This technology uses a high-energy laser beam to melt metal powder layer by layer, directly forming complex structural parts. It offers significant design freedom, high material utilization, and a short product development cycle. Compared to traditional manufacturing methods, laser additive manufacturing (LAM) can achieve dimensional accuracy of 0.1mm and surface quality of Ra30-50µm, making it particularly suitable for complex structural parts that are difficult to process using traditional methods. However, during the laser additive manufacturing process of manganese-copper alloys, the powder undergoes a non-equilibrium thermal cycle of rapid melting and solidification, which is highly susceptible to defects such as incomplete fusion, pores, and solidification cracks. Manganese-copper alloys with high manganese content, which offer wide-temperature vibration and noise reduction performance, exhibit increased crack sensitivity, which not only severely impacts the material's mechanical properties but also significantly reduces its damping capacity, significantly limiting their practical application in engineering vibration reduction. While optimizing printing process parameters such as laser power and scanning speed can alleviate residual stress and cracking to some extent, completely eliminating solidification cracks is difficult. Therefore, how to reduce the solidification crack sensitivity of laser additively manufactured manganese-copper alloys and prepare high-performance additively manufactured manganese-copper alloys is a technical problem that needs to be solved urgently.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of the present invention is to provide an additively manufactured manganese-copper alloy and its preparation method and application to improve the above-mentioned technical problems.

[0007] The present invention is achieved in that: In a first aspect, the present invention provides a method for preparing a manganese-copper alloy by additive manufacturing, comprising: After placing manganese-copper-nickel alloy powder on a substrate, preheating the substrate, and subjecting the manganese-copper-nickel alloy powder to laser selective melting in a forming chamber to obtain a manganese-copper alloy sample; Among them, the chemical composition of the manganese-copper-nickel alloy powder is, by mass percentage, Cu 10%~25%, Ni 3%~10%, C≤0.03%, Si≤0.02%, S≤0.02%, P≤0.005%, and the balance is Mn element and other inevitable impurities; the parameters of the laser selective melting are: laser power of 80W-300W, scanning speed of 300mm / s~1200mm / s, scanning spacing of 0.06mm~0.16 mm, powder thickness of 0.04mm~0.10mm, scanning interval time of 30s~120s, and the laser scanning strategy is strip 67° or chessboard 67°.

[0008] In an optional embodiment, the laser power is 120W-150W, the scanning speed is 700mm / s~900mm / s, the scanning spacing is 0.13mm~0.15mm, the powder thickness is 0.07mm~0.09mm, and the scanning interval time is 60s~110s.

[0009] In an optional embodiment, the laser power is 130W-150W, the scanning speed is 800mm / s~900mm / s, the scanning spacing is 0.13mm~0.15mm, the powder thickness is 0.07mm~0.09mm, and the scanning interval time is 70s~100s.

[0010] In an optional embodiment, the laser scanning strategy uses a checkerboard 67°.

[0011] In an optional embodiment, the chemical composition of the manganese-copper-nickel alloy powder is: Cu 13%~18%, Ni 6%~10%, C≤0.03%, Si≤0.02%, S≤0.02%, P≤0.005%, and the balance is Mn element and other inevitable impurities.

[0012] In an optional embodiment, the substrate is preheated to a temperature of 100°C to 300°C, preferably 150°C to 200°C.

[0013] In an optional embodiment, the manganese-copper-nickel alloy powder is obtained by mechanically mixing manganese-copper alloy powder and nickel powder. Preferably, the manganese-copper alloy powder and the nickel powder are prepared by vacuum air atomization.

[0014] In an optional embodiment, the composition of the substrate is consistent with the composition of the manganese-copper-nickel alloy powder.

[0015] In a second aspect, the present invention further provides an additively manufactured manganese-copper alloy, which is prepared by the preparation method described in any one of the aforementioned embodiments.

[0016] In a third aspect, the present invention also provides the application of the additively manufactured manganese-copper alloy as described in the aforementioned embodiment in automobiles, ships, weapons and equipment, or aerospace.

[0017] The present invention has the following beneficial effects: a manganese-copper alloy is prepared using selective laser melting technology. The composition of the manganese-copper alloy is optimized by adding nickel. Combined with optimized printing process parameters, control of substrate preheating temperature and scanning interval time, and scanning strategy, the alloy microstructure can be effectively regulated, helping to reduce residual stress generated during laser rapid cooling and effectively eliminating solidification cracks generated during printing. This allows the alloy to have good forming quality and density while also combining good damping and mechanical properties. This method achieves the one-step preparation of a high-performance manganese-copper damping alloy without the need for post-heat treatment, effectively reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 Schematic diagram of the selected laser scanning strategy; Figure 2 Metallographic photographs of the manganese-copper alloy samples prepared in Examples 1-6 and Comparative Examples 1-6. DETAILED DESCRIPTION

[0020] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.

[0021] The following is a detailed description of an additively manufactured manganese-copper alloy provided by the present invention, as well as its preparation method and application.

[0022] Some embodiments of the present invention provide a method for additively manufacturing a manganese-copper alloy, comprising: After placing manganese-copper-nickel alloy powder on a substrate, preheating the substrate, and subjecting the manganese-copper-nickel alloy powder to laser selective melting in a forming chamber to obtain a manganese-copper alloy sample; Among them, the chemical composition of the manganese-copper-nickel alloy powder is, by mass percentage, Cu 10%~25%, Ni 3%~10%, C≤0.03%, Si≤0.02%, S≤0.02%, P≤0.005%, and the remainder is Mn element and other inevitable impurities; the parameters of the laser selective melting are: laser power of 80W-300W, scanning speed of 300mm / s~1200mm / s, scanning spacing of 0.06mm~0.16mm, powder thickness of 0.04mm~0.10mm, scanning interval time of 30s~120s, and the laser scanning strategy is strip 67° or chessboard 67°.

[0023] By optimizing the chemical composition of the manganese-copper alloy and adjusting the parameters of the selective laser melting process to control the alloy's microstructure, the team specifically adjusted the scanning interval and scanning strategy to reduce the residual stress formed during the rapid melting and solidification process of the manganese-copper alloy powder, eliminating solidification cracks in the manganese-copper alloy and imparting excellent forming quality, damping, and mechanical properties. Furthermore, the above method allows for the one-step preparation of a high-performance manganese-copper damping alloy, eliminating the need for post-heat treatment steps such as aging, effectively reducing costs.

[0024] In some embodiments, the method for preparing manganese-copper alloy by additive manufacturing specifically comprises the following steps: S1. Prepare manganese-copper-nickel alloy powder.

[0025] Manganese-copper-nickel alloy powder can be obtained by mechanically mixing manganese-copper alloy powder and nickel powder. Manganese-copper alloy powder and nickel powder are independently prepared, preferably using vacuum gas atomization. This method produces manganese-copper alloy powder and nickel powder with good sphericity, which can improve the uniformity of the prepared alloy product.

[0026] It should be noted that vacuum air atomization powder making is an existing process for preparing alloy powder.

[0027] In some embodiments, the manganese-copper alloy powder includes, by mass percentage, Cu 13%-15%, C≤0.03%, Si≤0.02%, S≤0.02%, P≤0.005%, and the balance is Mn element and other unavoidable impurities; the purity of the nickel powder is greater than 99.9%; by optimizing the composition of the manganese-copper alloy powder, the molding quality of the manganese-copper alloy product can be further improved.

[0028] Specifically, the copper content may be 13%, 14%, 15%, etc., and the Ni content may be 1%, 3%, 5%, 7%, 10%, etc.

[0029] In some embodiments, the manganese-copper alloy powder and the nickel powder are mechanically mixed by a V-type powder mixer to make the distribution of the components more uniform, which is beneficial to improving the subsequent printing effect.

[0030] In some embodiments, the particle size range of the manganese-copper alloy powder and the nickel powder is 15 μm-53 μm, which can control the particle size of the manganese-copper-nickel alloy powder within the above range, and can make the powder have low oxygen content and good sphericity. The flowability of the manganese-copper-nickel alloy powder is 22s / 50g-35s / 50g, and the bulk density is 3.3g / cm 3 -4.2g / cm 3 By controlling the powder's fluidity and apparent density, the powder is easily melted to meet experimental requirements. Manganese-copper alloy powder and nickel powder exhibit excellent fluidity, sphericity, and apparent density. Laser selective melting allows for a short cycle time and direct forming. The printed manganese-copper alloy can achieve a density of up to 99.8%.

[0031] For example, the particle size range of the manganese-copper-nickel alloy powder can be a range between any two values ​​such as 15 μm, 25 μm, 35 μm, 45 μm, 53 μm, etc., the fluidity of the manganese-copper alloy powder can be 22 s / 50 g, 24 s / 50 g, 26 s / 50 g, 28 s / 50 g, 30 s / 50 g, 33 s / 50 g, etc., and the bulk density of the manganese-copper alloy powder can be 3.3 g / cm 3 , 3.5g / cm 3 、3.7g / cm 3 、3.9g / cm 3 , 4.2g / cm 3 wait.

[0032] It should be noted that the fluidity of metal powder refers to the time required for a certain amount of powder to flow through a standard funnel with a specified aperture, which is the time it takes for 50g of standard substance to flow on a new funnel. For specific reference, please refer to: GB / T 1482-2022 Metal Powder Fluidity Determination Standard Funnel Method (Hall Rheometer).

[0033] Furthermore, in order to achieve better forming quality and damping and mechanical properties, the chemical composition of the manganese-copper-nickel alloy powder can be optimized as follows: Cu 13%~18%, Ni 6%~10%, C≤0.03%, Si≤0.02%, S≤0.02%, P≤0.005%, and the remainder is Mn element and other inevitable impurities.

[0034] S2. Preparation of manganese-copper alloy samples by laser selective melting process.

[0035] Specifically, manganese-copper alloy powder is laid onto a homogeneous printed substrate within a forming chamber and preheated. A laser is then applied as a heat source to perform selective laser melting on the printed substrate to produce a manganese-copper alloy specimen. After printing, the manganese-copper alloy can be cut from the substrate using wire-cut electric discharge equipment and cut into the required metallographic specimens (10 mm x 10 mm x 10 mm) according to the required dimensions. The above dimensions are based on, but are not limited to, length, width, and height.

[0036] In some embodiments, the printing substrate is preheated before printing begins to reduce thermal stress and defects during the printing process. The surface temperature of the preheated substrate is higher. When the first layer of powder is melted by the laser, the molten metal can better infiltrate the surface of the substrate, reducing "unfused" defects, ensuring the connection strength between the bottom of the part and the substrate, and improving the molding quality and stability of the part.

[0037] Specifically, the substrate is preheated to a temperature of 100° C. to 300° C., preferably 150° C. to 200° C. For example, the preheating temperature may be 150° C., 175° C., 200° C., etc.

[0038] In some embodiments, the composition of the substrate is consistent with the composition of the manganese-copper-nickel alloy powder to ensure wettability between the raw material powder and the substrate.

[0039] In some embodiments, the selective laser melting (SLM) printing equipment employed may be the German-made EOS M290 printer, which comprises a powder spreading system, scanning system, laser, gas shielding system, and optical system. The EOS M290 system is equipped with a 400W fiber laser, providing a high-performance, highly stable, and high-quality laser light source. This equipment is compatible with both nitrogen and argon shielding gases, making the M290 system compatible with a variety of metal materials, including stainless steel, high-temperature alloys, and tool steel.

[0040] In some embodiments, the forming process parameters are optimized as follows: laser power is 120W-150W, scanning speed is 700mm / s~900mm / s, scanning spacing is 0.13mm~0.15mm, powder thickness is 0.07mm~0.09mm, and scanning interval time is 60s~110s.

[0041] In some embodiments, the optimization is further as follows: laser power is 130W-150W, scanning speed is 800mm / s~900mm / s, scanning spacing is 0.13mm~0.15mm, powder thickness is 0.07mm~0.09mm, and scanning interval time is 70s~100s.

[0042] By controlling the above forming parameters, the microstructure of the manganese-copper alloy can be regulated, the residual stress of the alloy can be reduced, and the forming quality and density of the manganese-copper alloy can be improved, thereby eliminating the solidification cracks generated during the preparation process.

[0043] In some embodiments, a checkerboard 67° laser scanning strategy is used. This specific scanning method can significantly reduce interlaminar stress through thermal isolation. A specific scanning angle can inhibit the accumulation of thermal stress, thereby reducing solidification cracks during the fabrication process and improving the mechanical and damping properties of the material.

[0044] In some embodiments, the obtained block-shaped printed manganese-copper alloy sample can be surface treated before microstructural observation. The surface treatment can be performed by polishing the surface of the block-shaped printed manganese-copper alloy sample using 400#, 600#, 800#, 1000#, or 1500# silicon carbide sandpaper, then mechanically polishing it using a woolen polishing cloth, cleaning the surface with anhydrous ethanol, and finally drying the surface with a hair dryer.

[0045] Some embodiments of the present invention further provide an additively manufactured manganese-copper alloy, which is prepared by the preparation method described in any of the aforementioned embodiments. The manganese-copper alloy has good molding quality and density.

[0046] Some embodiments of the present invention also provide applications of the additively manufactured manganese-copper alloy described in the aforementioned embodiments in automobiles, ships, weapons and equipment, or aerospace.

[0047] The features and performance of the present invention are further described in detail below with reference to the embodiments.

[0048] Example 1 This embodiment provides a method for preparing a manganese-copper alloy by additive manufacturing, comprising the following steps: (1) Powder preparation Manganese-copper alloy powder and nickel powder were prepared by gas atomization method, and the alloy powder was sieved. The particle size range of the powder was 15μm~53μm.

[0049] Calculated by mass percentage, the manganese-copper alloy powder includes: Cu 15%, C 0.02%, Si 0.015%, S 0.015%, P 0.003%, and the balance is Mn element and other inevitable impurities.

[0050] Manganese-copper alloy powder and 3 wt % nickel powder were mechanically mixed for 12 h using a V-type powder mixer to obtain manganese-copper-nickel powder.

[0051] (2) Preparation of manganese-copper alloy samples by laser selective melting process The selected laser melting process parameters were set as follows: laser power of 100 W, scanning speed of 500 mm / s, scanning pitch of 0.1 mm, powder layer thickness of 0.05 mm, printing strategy of 67° strip pattern, and laser scanning interval of 50 seconds. Powder was placed in the powder feed cylinder of the printing device, and the substrate was heated to 150°C before forming the manganese-copper alloy.

[0052] Example 2 This embodiment provides a method for preparing a manganese-copper alloy by additive manufacturing, comprising the following steps: (1) Powder preparation Manganese-copper alloy and nickel powders were prepared by gas atomization method, and the alloy powders were sieved. The particle size range of the powders was 15μm~53μm.

[0053] Calculated by mass percentage, the manganese-copper alloy powder includes: Cu 15%, C 0.02%, Si 0.015%, S 0.015%, P 0.003%, and the balance is Mn element and other inevitable impurities.

[0054] Manganese-copper alloy powder and 5 wt % nickel powder were mechanically mixed for 12 h using a V-type powder mixer to obtain manganese-copper-nickel powder.

[0055] (2) Preparation of manganese-copper alloy samples by laser selective melting process The selected laser melting process parameters were set as follows: laser power of 100 W, scanning speed of 600 mm / s, scanning pitch of 0.12 mm, powder layer thickness of 0.06 mm, scanning strategy of 67° stripe pattern, and laser scanning interval of 60 seconds. Powder was placed in the powder feed cylinder of the printing device, and the substrate was heated to 175°C before forming the manganese-copper alloy.

[0056] Example 3 This embodiment provides a method for preparing a manganese-copper alloy by additive manufacturing, comprising the following steps: (1) Powder preparation Manganese-copper alloy and nickel powders were prepared by gas atomization method, and the alloy powders were sieved. The particle size range of the powders was 15μm~53μm.

[0057] Calculated by mass percentage, the manganese-copper alloy powder includes: Cu 15%, C 0.02%, Si 0.015%, S 0.015%, P 0.003%, and the balance is Mn element and other inevitable impurities.

[0058] Manganese-copper alloy powder and 7 wt % nickel powder were mechanically mixed for 12 h using a V-type powder mixer to obtain manganese-copper-nickel powder.

[0059] (2) Preparation of manganese-copper alloy samples by laser selective melting process The selected laser melting process parameters were set as follows: laser power of 120 W, scanning speed of 700 mm / s, scanning pitch of 0.14 mm, powder layer thickness of 0.07 μm, scanning strategy of 67° strip pattern, and laser scanning interval of 70 seconds. Powder was placed in the powder feed cylinder of the printing device, and the substrate was heated to 175°C before forming the manganese-copper alloy.

[0060] Example 4 This embodiment provides a method for preparing a manganese-copper alloy by additive manufacturing, comprising the following steps: (1) Powder preparation Manganese-copper alloy and nickel powders were prepared by gas atomization method, and the alloy powders were sieved. The particle size range of the powders was 15μm~53μm.

[0061] Calculated by mass percentage, the manganese-copper alloy powder includes: Cu 15%, C 0.02%, Si 0.015%, S 0.015%, P 0.003%, and the balance is Mn element and other inevitable impurities.

[0062] Manganese-copper alloy powder and 10 wt % nickel powder were mechanically mixed for 12 h using a V-type powder mixer to obtain manganese-copper-nickel powder.

[0063] (2) Preparation of manganese-copper alloy samples by laser selective melting process The selected laser melting process parameters were set as follows: laser power of 140 W, scanning speed of 800 mm / s, scanning pitch of 0.14 mm, powder layer thickness of 0.08 mm, a 67° checkerboard scanning strategy, and a laser scanning interval of 70 seconds. The powder was placed in the powder feed cylinder of the printing device, and the substrate was heated to 200°C before forming the manganese-copper alloy.

[0064] Example 5 This embodiment provides a method for preparing a manganese-copper alloy by additive manufacturing, comprising the following steps: (1) Powder preparation Manganese-copper alloy and nickel powders were prepared by gas atomization method, and the alloy powders were sieved. The particle size range of the powders was 15μm~53μm.

[0065] Calculated by mass percentage, the manganese-copper alloy powder includes: Cu 15%, C 0.02%, Si 0.015%, S 0.015%, P 0.003%, and the balance is Mn element and other inevitable impurities.

[0066] Manganese-copper alloy powder and 10 wt % nickel powder were mechanically mixed for 12 h using a V-type powder mixer to obtain manganese-copper-nickel powder.

[0067] (2) Preparation of manganese-copper alloy samples by laser selective melting process The selected laser melting process parameters were set as follows: laser power of 140 W, scanning speed of 900 mm / s, scanning pitch of 0.14 mm, powder layer thickness of 0.08 mm, a 67° checkerboard scanning strategy, and a laser scanning interval of 100 seconds. The powder was placed in the powder feed cylinder of the printing device, and the substrate was heated to 200°C before forming the manganese-copper alloy.

[0068] Example 6 This embodiment provides a method for preparing a manganese-copper alloy by additive manufacturing, comprising the following steps: (1) Powder preparation Manganese-copper alloy and nickel powders were prepared by gas atomization method, and the alloy powders were sieved. The particle size range of the powders was 15μm~53μm.

[0069] Calculated by mass percentage, the manganese-copper alloy powder includes: Cu 15%, C 0.02%, Si 0.015%, S 0.015%, P 0.003%, and the balance is Mn element and other inevitable impurities.

[0070] Manganese-copper alloy powder and 10 wt % nickel powder were mechanically mixed for 12 h using a V-type powder mixer to obtain manganese-copper-nickel powder.

[0071] (2) Preparation of manganese-copper alloy samples by laser selective melting process The selected laser melting process parameters were set as follows: laser power of 140 W, scanning speed of 900 mm / s, scanning pitch of 0.14 mm, powder layer thickness of 0.08 mm, scanning strategy of 67° stripe pattern, and laser scanning interval of 100 seconds. Powder was placed in the powder feed cylinder of the printing device, and the substrate was heated to 200°C before forming the manganese-copper alloy.

[0072] Comparative Example 1 This embodiment provides a method for preparing a manganese-copper alloy by additive manufacturing, comprising the following steps: (1) Powder preparation Manganese-copper alloy powder was prepared by gas atomization method, and the alloy powder was sieved. The particle size range of the powder was 15μm~53μm.

[0073] Calculated by mass percentage, the manganese-copper alloy powder includes: Cu 15%, C 0.02%, Si 0.015%, S 0.015%, P 0.003%, and the balance is Mn element and other inevitable impurities.

[0074] (2) Preparation of manganese-copper alloy samples by laser selective melting process The laser selective melting process parameters were set to: 100W laser power, 500mm / s scanning speed, 0.1mm scanning pitch, 0.05mm powder thickness, 67° strip printing strategy, and 50s laser scanning interval. Powder was placed in the powder feed cylinder of the printing device, the substrate was heated to 150°C, and then the manganese-copper alloy was formed.

[0075] Comparative Example 2 The only difference from Example 2 is that the homogeneous substrate is not preheated in this comparative example.

[0076] Comparative Example 3 The only difference from Example 3 is that the setting values ​​of the laser selective melting forming process parameters in this comparative example are: laser power is 500 W, scanning speed is 1500 mm / s, scanning spacing is 0.04 mm, and powder thickness is 0.03 mm.

[0077] Comparative Example 4 The only difference from Example 4 is that the scanning strategy selected in this comparative example is chessboard 0°.

[0078] Comparative Example 5 The only difference from Example 5 is that the laser scanning interval time in this comparative example is 0s.

[0079] Comparative Example 6 The only difference from Example 5 is that the laser scanning interval in this comparative example is 25 seconds.

[0080] Among them, in the above embodiments and comparative examples, the scanning strategies of stripe type 67°, chessboard type 0° and chessboard type 67° are as follows: Figure 1 shown.

[0081] Experimental example The manganese-copper alloys prepared in Examples 1-6 and Comparative Examples 1-6 were observed for defects by metallography and their relative densities were calculated using ImageJ software. The damping and tensile properties at room temperature were measured using a thermodynamic mechanical analyzer and a universal servo machine. The experimental results are shown in Tables 1, 2, 3 and Figure 2 shown.

[0082] Table 1 Density results of manganese-copper alloy

[0083] Table 2 Strain amplitude of additively manufactured manganese-copper alloy at room temperature =8×10 -4 Damping performance

[0084] Table 3 Tensile test results of manganese-copper alloy

[0085] As can be seen from Table 1, the manganese-copper alloys prepared in Examples 1-6 have a relatively high density, up to 99.8%. However, the manganese-copper alloys prepared in Comparative Examples 1-6 (no Ni addition, no substrate preheating, laser power of 500 W, scanning speed of 1500 mm / s, scanning spacing of 0.04 mm, powder thickness of 0.03 mm, chessboard scanning strategy of 0°, and laser interval time of no more than 25 s) have relatively low density or poor damping and mechanical properties. Figure 2 It can be seen that there are a large number of cracks in Comparative Example 1 and the relative density is the lowest. As can be seen from Table 2, the manganese-copper alloys prepared in Examples 1-6 have good damping properties. Compared with Comparative Examples 1-6, the damping properties of the manganese-copper alloys prepared in Examples 1-6 are improved by 15-155%. In particular, Example 5 has much better damping properties than Comparative Examples 1-6. As can be seen from Table 3, the manganese-copper alloys prepared in Examples 1-6 have good mechanical properties. Compared with Comparative Examples 1-6, the manganese-copper alloys prepared in Examples 1-6 have a yield strength increased by 7-90%, a tensile strength increased by 10-43%, and an elongation after fracture increased by 20%-60%.

[0086] In summary, the embodiment of the present invention uses manganese-copper alloy powder and nickel powder as raw materials, and prepares manganese-copper-nickel alloy powder by an in-situ powder mixing process to optimize the alloy composition; selects a homogeneous manganese-copper alloy substrate and preheats it; uses laser selective melting technology to prepare manganese-copper alloy, and reasonably controls printing parameters, laser scanning strategy and scanning interval time; combines alloying with optimized printing process, regulates the alloy microstructure, reduces the residual stress formed in the manganese-copper alloy powder during the express and solidification process, eliminates the solidification cracks of the manganese-copper alloy, and makes the manganese-copper alloy have good forming quality and good damping and mechanical properties.

[0087] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A method for preparing manganese-copper alloy by additive manufacturing, characterized in that: It includes: After placing manganese-copper-nickel alloy powder on a substrate, preheating the substrate, and subjecting the manganese-copper-nickel alloy powder to laser selective melting in a forming chamber to obtain a manganese-copper alloy sample; Among them, the chemical composition of the manganese-copper-nickel alloy powder is, by mass percentage, Cu 10%~25%, Ni 3%~10%, C≤0.03%, Si≤0.02%, S≤0.02%, P≤0.005%, and the balance is Mn element and other inevitable impurities; the parameters of the laser selective melting are: laser power of 80W-300W, scanning speed of 300mm / s~1200mm / s, scanning spacing of 0.06mm~0.16 mm, powder thickness of 0.04mm~0.10mm, scanning interval time of 30s~120s, and the laser scanning strategy is strip 67° or chessboard 67°.

2. The preparation method according to claim 1, characterized in that The laser power is 120W-150W, the scanning speed is 700mm / s-900mm / s, the scanning spacing is 0.13mm-0.15mm, the powder thickness is 0.07mm-0.09mm, and the scanning interval time is 60s-110s.

3. The preparation method according to claim 2, characterized in that The laser power is 130W-150W, the scanning speed is 800mm / s-900mm / s, the scanning spacing is 0.13mm-0.15mm, the powder thickness is 0.07mm-0.09mm, and the scanning interval time is 70s-100s.

4. The preparation method according to claim 1, characterized in that The laser scanning strategy uses a chessboard 67°.

5. The preparation method according to any one of claims 1 to 4, characterized in that The chemical composition of the manganese-copper-nickel alloy powder is: Cu 13%-18%, Ni 5%-10%, C≤0.03%, Si≤0.02%, S≤0.02%, P≤0.005%, and the balance is Mn element and other inevitable impurities.

6. The preparation method according to any one of claims 1 to 4, characterized in that The substrate is preheated to a temperature of 100° C. to 300° C.

7. The preparation method according to any one of claims 1 to 4, characterized in that The manganese-copper-nickel alloy powder is obtained by mechanically mixing manganese-copper alloy powder and nickel powder. The manganese-copper alloy powder and the nickel powder are prepared by using a vacuum air atomization method.

8. The preparation method according to any one of claims 1 to 4, characterized in that The composition of the substrate is consistent with the composition of the manganese-copper-nickel alloy powder.

9. An additively manufactured manganese-copper alloy, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the additively manufactured manganese-copper alloy according to claim 9 in automobiles, ships, weapons and equipment, or aerospace.

Citation Information

Patent Citations

  • Preparation method of manganese-copper damping alloy

    CN110172625A

  • Manganese-copper damping alloy powder for SLM process and preparation method thereof

    CN111057922A

  • Selective laser melting additive manufacturing method and additive manufacturing device for manganese-copper alloy forming

    CN111761064A

  • Manganese-copper alloy and additive manufacturing method and application thereof

    CN116550995A

  • MN-CU-Based Damping Alloy Powder For Use In Selective Laser Melting Process And Preparation Method Thereof

    US20210197277A1